Correction to: Intramural metastasis to the appendix from ascending colon cancer: a case report - Toshiya Abe; Hiroshi Sakai; Masataka Hayashi; So Nakamura; Shin Takesue; Masafumi Sada; Shingo Kozono; Yoshiki Kitaura; Yoshitaka Tanabe; Kazuyoshi Nishihara; Mari Mine; Sadafumi Tamiya; et al. (Surgical Case Reports, 2020)
In the original publication of this article [1], an author’s name should be changed from Shin Takasue to Shin Takesue.